Brazilian Jiu Jitsu players’ motivations to train - Tarver, Terrance L.; Levy, Jacob J. (Frontiers in Psychology, 2023)
Combat sports, such as Brazilian Jiu Jitsu (BJJ), require intense physical, mental, and emotional tasking within its training. With the degree of difficulty ingrained within the sport, many participants that once were intrigued by the sport may lose this interest and enjoyment if their goals are not met. The purpose of this study was to examine the relative strength of sport motivations among BJJ players. Participants included 228 BJJ athletes varying in levels of sport participation experience. Grounded in Self-Determination Theory, participants were assessed on five motives for sport participation including: fitness, appearance, competence, social, and interest/enjoyment. Motives related to interest/enjoyment, competence, and fitness, were rated relatively higher; and appearance and social were rated relatively lower regarding participants’ motivation for BJJ participation. Analyses were also conducted related to athletes’ years of experience and competitive level of participation (i.e., hobbyist or non-competitor to those who compete on a regular basis) There was a significant effect of competence and interest/enjoyment motivators among competitive BJJ players, regardless of years of experience in the sport. Findings from this study could aid coaches, sport clinicians, and sport psychologists in working with BJJ players by focusing their training on the motivators that are most appealing to these athletes.